Rapid fabrication of TiO2 nanobelts with controllable crystalline structure by microwave-assisted hydrothermal method and their photocatalytic activity. Issue 17 (1st December 2019) - Zhang, Meiyue; Wang, Wei; Wu, Chang; Wang, Pengwei; Ru, Hongqiang
Abstract: TiO2 nanobelts (NBs) have received much attention due to their chemical stability, nontoxicity, special one-dimension morphology and also have found many applications. However, extensively employed hydrothermal processes are time-consuming. In this work, a microwave-assisted hydrothermal (MAH) method is for the first time reported for the rapid fabrication of TiO2 NBs. TiO2 NBs with widths of 25–200 nm and lengths up to tens micrometers can be successfully fabricated by adjusting the concentration of NaOH solution, reaction time and reaction temperatures. By MAH method, the reaction time can be greatly shortened to 4 h under microwave irradiation compared to 1–3 days reported in literature. Bi-crystalline structures with monoclinic TiO2 (B) and tetragonal anatase can be tuned by simply adjusting thermal treatment temperatures. The evolution of different crystalline structures from starting H2 Ti3 O7 to crystalline TiO2 phases with increasing calcination temperatures was analyzed by different techniques. The photocatalytic activity results reveal that bi-crystalline structures with TiO2 (B)/anatase phases (optimal B:A ratio of 66:34) are advantageous to enhance the photocatalytic performance of TiO2 NBs in photo-decomposing Rhodamine B molecules in water under UV irradiation.